Ameliorating Amyloid-β Fibrils Triggered Inflammation via Curcumin-Loaded Polymeric Nanoconstructs - Ameruoso, Andrea; Palomba, Roberto; Palange, Anna Lisa; Cervadoro, Antonio; Lee, Aeju; Di Mascolo, Daniele; Decuzzi, Paolo (Frontiers in Immunology, 2017)
Inflammation is a common hallmark in several diseases including atherosclerosis, cancer, obesity and neurodegeneration. In Alzheimer’s disease, growing evidence directly correlates neuronal damage with inflammation of myeloid brain cells, such as microglia. Here, polymeric nanoparticles were engineered and characterized for the delivery of anti-inflammatory molecules to macrophages stimulated via direct incubation with amyloid-β fibers. 200 nm spherical polymeric nanoparticles (SPNs) and 1,000 nm discoidal polymeric nanoconstructs (DPNs) were synthesized using poly(lactic-co-glycolic acid) (PLGA), polyethylene glycol (PEG), and lipid chains as building blocks. First, the internalization propensity in macrophages of both nanoparticles was assessed via cytofluorimetric and confocal microscopy analyses, demonstrating that SPNs are by far more rapidly taken up as compared to DPNs (99.6±0,11% vs 14.4±0.06%, within 24h). Then, Curc-SPNs were realized by encapsulating curcumin, a natural anti-inflammatory molecule, within the PLGA core of SPNs. Finally, Curc-SPNs were shown to diminish up to 6.5-fold the production of pro-inflammatory cytokines – IL-1β; IL-6 and TNF-α – in macrophages stimulated via amyloid-β fibers. Although more sophisticated in vitro models and systematic analyses on the blood brain barrier permeability are critically needed, these preliminary findings hold potential in the development of nanoparticles for modulating inflammation in Alzheimer’s disease.